Book Review: Negotiating Women’s Veiling, Politic & Sexuality in Contemporary Indonesia - Qibtiyah, Alimatul (Musawa Jurnal Studi Gender dan Islam, 2014)
Judul Buku : Negotiating Women’s Veiling, Politic & Sexuality in Contemporary IndonesiaPenulis : Dewi CandraningrumPenerbit : @IRASEC, Juni 2013ISBN : 978-616-7571-15-7Tebal halaman : 89 halaman